Use Of Montmorillonite Bentonite Group Minerals for Balanced Mineral Nutrition. (Texas Journal of Multidisciplinary Studies, 2022)
Bentonite is a biologically active substance, adding it to feed and fertilizers to the soil increases the productivity of animals and the yield of agricultural crops. The main component of bentonite is montmorillonite. Bentonite clay is widely used in the medical and industrial fields. Being a source of irrigation microelements, bentonite is used for the manufacture of various dietary supplements and vitamins, it has a good effect on the functioning of the gastrointestinal tract, has a more soothing and anti-inflammatory effect. It is used as a dietary supplement for the prevention and treatment of aflotoxin toxicity. Bentonite is a reliable food supplement for metal poisoning. Montmorillonite crystals have fat-absorbing properties, it has antibacterial properties. Bentonite adsorbs and releases a strong toxic substance - gossypol. Preparations based on bentonites have the properties of an ion exchange adsorbent and a catalyst